ISOLATION AND IDENTIFICATION OF BACTERIA CAUSING BOVINE MASTITIS AS A FUNCTION OF LACTATION TIME IN DAIRY COWS FROM NORTHWESTERN PICHINCHA – ECUADOR - Joao Mazón-Vélez, Dagnny Mazón-Vélez, Riveliño Ramón-Curay, Favian Bayas-Morejón (Chelonian Research Foundation, 2023)
Bovine mastitis is a pathology that generates great economic losses worldwide, therefore it is of crucial importance to know the influence that certain microorganisms have during the lactation period. The objective of this study was to isolate and identify bacteria causing bovine mastitis and its contingency based on lactation time in dairy cows from the northwest of Pichincha - Ecuador. The California mastitis test (CMT) was the diagnostic method used for the determination of mastitis, together with bacterial isolation and identification procedures by means of phenotypic tests in selective and differential agars, as well as biochemical tests such as IMVIC profiles and sugar fermentation patterns, gas production and hydrogen sulfide production determined by the Triple Sugar Iron (TSI) test, also with oxidase, catalase and coagulase tests, likewise, observing that the data corresponding to the lactation time of each particular farm considered as the focus of the study, were in an average of 315 ± 6. 46 days. Seven dairy farms were examined, testing 136 cows in total, of which epidemiologically 50 cows were positive for mastitis, obtaining 51 milk samples, of which Staphylococcus aureus was isolated in 29.42%, Klebsiella spp. in 17. 64%, Bacillus spp. in 17.64%, Escherichia coli in 15.68%, coagulase-negative Staphylococcus spp. in 15.68%, and Citrobacter spp. in 3.94%, reporting that the presence of Gram-negative bacilli has a higher occurrence at the beginning of lactation and Staphylococcus aureus in the middle of the lactation period. Key words: Bacteria, Bovine mastitis, Lactation time, CMT.